Jugoslavija po Jugoslaviji - Velikonja, Mitja (Dve domovini, 2017)
Twenty-five years after the bloody collapse of socialist Yugoslavia, the urban walls of its successor states are still full of graffiti of two homelands: the present-day nation-states and the former Yugoslav federation. The main questions of the text - based on my longitudinal research and semiological (quantitative and qualitative) methodological approaches - are how, where and why Yugoslavia, its socialism, its antifascist roots and its leaders are (de)constructed, praised and condemned in this specific urban subculture. On the level of denotation, graffiti and street art can be divided into pro-Yugoslav and anti-Yugoslav, often directly confronted in graffiti-battles. On the level of connotation, three major ideological antagonisms appear: socialist federalism vs. nationalism, Tito vs. his opponents, and antifascism vs. fascism. Before presenting the final findings of the research, an analysis is made of the expressive strategies of this urban production, such as provocation and criticism, affirmation and continuity, territory marking, constant antagonisation and semiotic guerrillism.
Keywords: graffiti; grafiti; immigration and emigration; izseljevanje in priseljevanje; jugonostalgija; Jugoslavija; nacionalizem; nationalism; semiologija; semiology; street art; ulična umetnost; Yugonostalgia; Yugo-nostalgia; Yugoslavia